Susceptibility of apples to damage by Lygocoris communis and Lygus lineolaris (Hemiptera : Miridae) - Michaud, O.D.; Stewart, R.K.; Boivin, G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Damage to apples (cv. Mclntosh) caused by nymphs and adults of Lygocoris communis and Lygus lineolaris was evaluated by placing insects in sleeve-cages on apple-bearing branches. Each nymph of L. communis placed in the cage at petal fall damaged an average of 2.1 apples whereas each adult placed in the cage after fruit set damaged 2.0 apples. Damage by young nymphs (1st, 2nd and 3rd instars) was severe whereas damage caused by old nymphs (4th and 5th instars) and adults was light. Each over wintered adult of L. lineolaris damaged an average of 4.5 fruit clusters. Each adult damaged an average of 4.0 apples when they attacked from tight-cluster to full-bloom stage.